Divulgando a Física aplicada à Medicina para professores e estudantes do Ensino Médio - CUNHA, Julyanne Silva (Universidade Federal do Tocantins, 2021)
Although the Medical Physics has emerged just over a century, nowadays it’s active in all areas of medicine. However, the community who benefits from diagnostics and treatments don’t know its existence and don’t understand the physics’ importance at school. The purpose was show the impacts of Physics in Medicine from dissemination of scientific papers to secondary school students and recognize profile of future physics teachers of the UFT, about teaching through research relating this to their training curriculum. To fulfill this goal, a questionnaire was prepared and applied to most students of the fifth to eighth period of the course. A literature review of scientific articles was also done in the area of Medical Physics, among them four were chosen to prepare posters for dissemination in secondary school. The questionnaires showed the students participate events and scientific programs, recognize the importance of these actions to the pedagogical practice, but because they don’t knowing the duties of physics teacher, this knowledge is not taken to the classroom. Although few have said they intend to be teachers, the most recognize the importance of disclosure of medical physics in schools, the posters developed would allow this work was done. Is expected to in future works they may be applied to secondary school to assess how students answered to this teaching methodology. Keywords: Medical Physics. Physics teaching. Research. Scientific divulgation.